What has the Coalition Government done for the development of initial teacher education? (UCL Press, 2015)
The past five years have seen significant changes to the structures and content of routes to Qualified Teacher Status (QTS) in this country, and to the balance of contributions to these routes between schools and higher education (HE). Such developments do not always address emerging knowledge about the needs of beginner teachers; further, changes have implications for teacher further professional development as well as for the health of education research in this country. However, changes have catalysed overdue evaluation of more established routes and a priori thinking about how such needs could best be met. The Carter Review (DfE, 2014b) offers some useful ways forward that should be complemented by rigorous evaluation of the range of outcomes of initial teacher education over short, medium, and long terms, making full use of the evidence base.